Application of an overset mesh based numerical wave tank for modelling realistic free-surface hydrodynamic problems. (15th March 2019) - Chen, Hao; Qian, Ling; Ma, Zhihua; Bai, Wei; Li, Ye; Causon, Derek; Mingham, Clive
Abstract: This paper presents a numerical wave tank based on the overset mesh approach. Overset mesh is favourable to the moving mesh method owing to its ability to represent complex geometries whilst maintaining a good quality mesh, especially for large amplitude body motions. The numerical wave tank is developed by integrating a generic overset mesh functionality with an efficient wave generation library in OpenFOAM ® . A series of benchmark test cases, including 2D regular waves interacting with a floating cylinder and box-shaped body with superstructures, 2D water entry of a rigid wedge and a ship hull section as well as the heave decay of a point absorber wave energy converter and the lifeboat motion in regular waves, are carried out to evaluate the capabilities of the developed numerical wave tank. The computed solutions agree well with the experimental data and other reference results reported in the literature, which demonstrates the capability of the numerical wave tank for modelling flow around structures with complex geometries under various wave conditions. The parallel efficiency of the solver, effects of the overlapping area on the solution accuracy and comparisons with the results from a dynamic mesh are also discussed.